The Effect of Palm Pollen Extract on Sexual Disorders in Postmenopausal Women: A Randomized Clinical Trial - Marzeyeh Loripoor; Fatemeh Esmaeili; Reza Vazirinejad; Sasan Dan (Shiraz University of Medical Sciences, 2023)
Background: Considering the numerous nutritional and estrogenic compounds of palm pollen and their effect on sexual function, this study was performed to investigate the effect of palm pollen extract on sexual disorders in postmenopausal women.Methods: In this three-blind clinical trial, 110 postmenopausal women from December 2019 to December 2020 from Rafsanjan comprehensive health service centers were randomly assigned to two groups, using a lottery method. The intervention group received 300 mg capsule of palm pollen extract, and the control group received placebo for 4 weeks. Sexual disorders were assessed with a 6-item female sexual function index before, at the end of the intervention, and 4 weeks after the end of the intervention. Independent t-test, Chi-square and repeated measures ANOVA were used to analyze the data through SPSS software version 21. The statistically significant level was considered P value less than 0.05.Results: The mean scores of sexual disorders before the intervention in the intervention and control groups were 15.36±5.01 and 14.13±4.67 (P=0.68); at the end of the intervention, they were 15.18±4.50 and 14.22±3.91 (P=0.43) and 4 weeks after the end of the intervention we obtained 15.7±4.77 and 14.44±3.78, respectively (P=0.90).Conclusions: According to the results, daily consumption of 300 mg of date pollen extract had no effect on improving sexual disorders in postmenopausal women. Further studies in this field are suggested.Trial Registration Number: IRCT20160308026971N10